Evaluation of the influence of the speed, preload and span length on the contact forces in the interaction between the pantograph and the overhead conductor rail. (15th September 2021) - Simarro, Montserrat; Castillo, Juan J.; Cabrera, Juan A.; Postigo, S.
Highlights: Contact forces in the overhead conductor rail-pantograph interaction are studied. The higher the speed and span length, the higher the contact force fluctuations. Higher preloads contribute to more homogenous contact forces. The excitation of OCR natural frequencies dramatically affects the contact forces. A proper pantograph selection according to the operating conditions is advisable. Abstract: The Overhead Conductor Rail is one of the methods to transmit energy to a moving train. This power feeding system has some advantages compared to the conventional overhead catenary system. However, its use is still mainly limited to underground and tunnel train infrastructures, probably due to a lack of knowledge of the performance of this method in some operating conditions. This work is devoted to the study of the influence of the speed, preload, and span length on the contact forces in the interaction between the pantograph and the overhead conductor rail. Three different lumped-element models of commercially available pantographs and a finite element model of the overhead conductor rail have been used to carry out the simulations. The contact forces between each pantograph and the catenary have been obtained in all cases. The analysis of the results reveals that the higher the speed and span length are the higher the contact force fluctuations are. On the contrary, the increase in the preload leads to lower contact force oscillations provided no resonance effects are present.